THE PRICING EFFICIENCY OF LEVERAGED EXCHANGE‐TRADED FUNDS: EVIDENCE FROM THE U.S. MARKETS. (17th June 2013) - Charupat, Narat; Miu, Peter
Abstract We examine the pricing efficiency of leveraged exchange‐traded funds, whose goal is to generate daily returns that are in a positive or a negative multiple of the underlying index returns. We find that bull funds (i.e., those with positive multiples) tend to trade at a discount more often than bear funds (i.e., those with negative multiples) do. Also, price deviations of bull (bear) funds are negatively (positively) correlated with their underlying index returns. These behaviors are more pronounced in funds with high leverage ratios, and can be partly explained by the funds' daily exposure adjustments to maintain their leverage ratios.